Fluid restriction in patients with pulmonary arterial hypertension and right heart failure - Benjamin, Nicola; Resag, Carolin; Xanthouli, Panagiota; Harutyunova, Satenik; Eichstaedt, Christina; Egenlauf, Benjamin; Grünig, Ekkehard (Respiration, 2025)
Introduction: In pulmonary arterial hypertension (PAH), right heart (RH) failure is associated with high mortality and poor prognosis. The objective of this cohort study was to assess, whether reduction of fluid intake is associated with RH size and clinical outcome in PAH patients. Methods: A retrospective, exploratory analysis of patients with invasively diagnosed PAH and signs of fluid retention who were routinely clinically monitored for 8.4 ± 5.3 months including fluid uptake and signs of RH failure was performed. Patients were advised to reduce fluid uptake to a maximum of 2 L per day (L/day) according to clinical routine. Clinical characteristics of patients with normal fluid intake <2 L/day vs. high fluid intake ≥2 L/day and patients who reduced vs. patients with increased fluid intake during follow-up were compared. Furthermore, the influence of hospitalization due to fluid overload and for treatment with intravenous diuretics at baseline and fluid intake on survival and time to clinical worsening (TTCW) were investigated. Results: Out of 66 patients with signs of fluid retention at baseline (normal fluid intake <2 L/day, n = 16; high fluid intake ≥2 L/day, n = 50), 21 presented with hospitalization due to fluid overload, which was significantly associated with worse survival (p = 0.004) and TTCW (p < 0.001). During follow-up patients who reduced fluid intake <2 L/day presented with in trend reduced right ventricular area (p = 0.051) and longer TTCW (p = 0.007). Hospitalization due to fluid overload and fluid intake during follow-up were independent predictors of TTCW. Conclusion: Restriction of fluid intake in PAH patients was highly effective and associated with significantly longer TTCW. Further evaluation of fluid restriction in PAH patients is needed in larger studies.